2012
DOI: 10.5581/1516-8484.20120031
|View full text |Cite
|
Sign up to set email alerts
|

Use of complementary and alternative medicine by patients with hematological diseases: experience at a university hospital in northeast Mexico

Abstract: BackgroundComplementary and alternative medicine includes a diverse group of medical and healthcare systems, practices and products not considered part of conventional medicine. Although there is information on unconventional practices in oncological diseases, specific data regarding the use of complementary and alternative medicine by hematology patients is scarce.ObjectiveThe aim of this study is to document the prevalence of this modality of unconventional therapy in patients with malignant and benign hemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
(28 reference statements)
0
5
0
3
Order By: Relevance
“…Differences in CAM intake according to gender have been found in some publications [21][22][23] , with a study conducted in Mexico in 2006 in patients with oncological disease in the private practice standing out. This study found the highest use of this type of therapies in young women with advanced disease, with the majority of CAM users being those who had been diagnosed with breast cancer (88%) 20 . Similar results have been reported in cancer patients in Malaysia (n = 200) 24 , and in Scottish, Australian and North American women [25][26][27] .…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Differences in CAM intake according to gender have been found in some publications [21][22][23] , with a study conducted in Mexico in 2006 in patients with oncological disease in the private practice standing out. This study found the highest use of this type of therapies in young women with advanced disease, with the majority of CAM users being those who had been diagnosed with breast cancer (88%) 20 . Similar results have been reported in cancer patients in Malaysia (n = 200) 24 , and in Scottish, Australian and North American women [25][26][27] .…”
Section: Discussionmentioning
confidence: 66%
“…A recent meta-analysis that included 39 studies, reports that the proportion of cancer patients who used CAM at the time of the survey is between 9 and 88%, and the combined proportion was 40% [95% CI: 33-47%] 15 . Considering the publications on Mexican population, a survey of pediatric cancer patients' relatives reported 70% of CAM use 19 and another study involving patients with hematological malignancies in a hospital of northern Mexico reported a prevalence of 64.7% 20 . In the present study, a prevalence of use of 80.3% was found, with this result being within previously published ranges.…”
Section: Discussionmentioning
confidence: 99%
“…Un metaanálisis reciente que consideró 39 estudios reporta que la proporción de pacientes con cáncer que usan MAC al momento de la encuesta está entre el 9 y el 88% y la proporción combinada fue del 40% [IC 95%: 33-47%] 15 . Considerando las publicaciones en población mexicana, una encuesta realizada a familiares de pacientes pediátricos con cáncer reporta un 70% de uso de MAC 19 y otro estudio en pacientes con enfermedad hematológica maligna en un hospital en el norte de México informa una prevalencia de 64.7% 20 . En el presente estudio se encontró una prevalencia de uso del 80.3%, por lo que este resultado está dentro de los rangos previamente publicados.…”
Section: Discussionunclassified
“…En el presente estudio se encontró una prevalencia de uso del 80.3%, por lo que este resultado está dentro de los rangos previamente publicados. La diferencia en la ingesta de MAC según sexo se ha hallado en algunas publicaciones [21][22][23] , destacándose el estudio realizado en México en 2006 en pacientes con enfermedad oncológica en la práctica privada, que encontró el mayor uso de este tipo de terapias en mujeres jóvenes con enfermedad avanzada, siendo la mayoría de las que usaron MAC aquellas con diagnóstico de cáncer de mama (88%) 20 , resultados similares se han reportado en pacientes con cáncer en Malasia (n = 200) 24 , en mujeres escocesas, australianas y estadounidenses [25][26][27] . En este estudio la diferencia en la ingesta de MAC según sexo y tipo de diagnóstico coincide con estos hallazgos, siendo más frecuente en las mujeres, en el grupo de edad de menores de 34 y de 55 a 66 años y con cáncer de mama, aunque las diferencias no fueron estadísticamente significativas.…”
Section: Discussionunclassified
“…Ramadan), 13 use of spiritual healing by patients with hematological diseases 14 and refusal of blood by Jehovah's Witnesses 15 …”
mentioning
confidence: 99%